2009
DOI: 10.1002/ana.21526
|View full text |Cite
|
Sign up to set email alerts
|

Taurine deficiency is a cause of vigabatrin‐induced retinal phototoxicity

Abstract: Objective Although vigabatrin irreversibly constricts the visual field, it remains a potent therapy for infantile spasms and a third-line drug for refractory epilepsies. In albino animals, this drug induces a reduction in retinal cell function, retinal disorganisation and cone photoreceptor damage. The objective of this study was to investigate the light dependence of the vigabatrin-elicited retinal toxicity and to screen for molecules preventing this secondary effect of vigabatrin. Methods Rats and mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
112
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 39 publications
10
112
2
3
Order By: Relevance
“…It has been demonstrated that seizures induced by pilocarpine produces changes in oxidative metabolism and interacts with glutamatergic receptors to produced part of its stimulatory action on the central nervous system [24][25][26][27] . The fall in glutamate content, after pretreatment with lipoic acid, is most readily explained as a consequence of inhibiting their release or increasing their metabolization [28][29][30] . Moreover, the lipoic acid can reduce the metabolization rate and/or augment the release and syntheses of neuroprotective taurine, suggesting a protective action of this amino acid against the excitotoxicity mediated by glutamate during seizures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that seizures induced by pilocarpine produces changes in oxidative metabolism and interacts with glutamatergic receptors to produced part of its stimulatory action on the central nervous system [24][25][26][27] . The fall in glutamate content, after pretreatment with lipoic acid, is most readily explained as a consequence of inhibiting their release or increasing their metabolization [28][29][30] . Moreover, the lipoic acid can reduce the metabolization rate and/or augment the release and syntheses of neuroprotective taurine, suggesting a protective action of this amino acid against the excitotoxicity mediated by glutamate during seizures.…”
Section: Discussionmentioning
confidence: 99%
“…One study in rodents showed that vigabatrin-associated retinopathy is associated with light exposure [72]. More recently, it has been suggested that a deficiency of taurine is implicated in the pathogenic process of vigabatrinassociated retinopathy [73,74]. A pharmacogenetic exploration of vigabatrin-induced visual field constriction has also been undertaken, although no clear association has been identified [75].…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…These MRI abnormalities may occur as early as 3 months after the initiation of therapy. They may be, in rare cases, accompanied by movement disorders [73]. Susceptibility seems to be restricted to infancy.…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…Estudos sugerem que a vigabatrina produz seus efeitos anticonvulsivantes por meio da diminuição da atividade da enzima GABA-transaminase 28 , pelo aumento da liberação do GABA e pela diminuição da concentração da dopamina e taurina cerebral 29 . A vigabatrina pode exercer efeito neuroprotetor contra o dano neuronal produzido pelo aumento no conteúdo de radicais livres durante as crises convulsivas.…”
Section: Discussionunclassified